2005
DOI: 10.1086/426384
|View full text |Cite
|
Sign up to set email alerts
|

Five New Extrasolar Planets

Abstract: We report multiple Doppler measurements of five nearby FGK main-sequence stars and subgiants obtained during the past 4-6 yr at the Keck Observatory. These stars, namely, HD 183263, HD 117207, HD 188015, HD 45350, and HD 99492, all exhibit coherent variations in their Doppler shifts consistent with a planet in Keplerian motion. The five new planets occupy known realms of planetary parameter space, including a wide range of orbital eccentricities, e ¼ 0 0:78, and semimajor axes, 0.1-3.8 AU, that provide further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
209
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(212 citation statements)
references
References 62 publications
3
209
0
Order By: Relevance
“…In four cases there are major updates to previously published orbital parameters, which we detail below. Marcy et al (2005) announced an M sin i = 3.7 M Jup planet in a 634-day, eccentric (e = 0.4) orbit around HD 183263, a G2 IV star, and pointed out a strong residual linear trend of 32 m s −1 yr −1 . Wright et al (2007) showed that by 2007 the residuals had significant curvature, but could not constrain the minimum mass of the outer companion.…”
Section: New and Updated Multiplanet Systemsmentioning
confidence: 99%
“…In four cases there are major updates to previously published orbital parameters, which we detail below. Marcy et al (2005) announced an M sin i = 3.7 M Jup planet in a 634-day, eccentric (e = 0.4) orbit around HD 183263, a G2 IV star, and pointed out a strong residual linear trend of 32 m s −1 yr −1 . Wright et al (2007) showed that by 2007 the residuals had significant curvature, but could not constrain the minimum mass of the outer companion.…”
Section: New and Updated Multiplanet Systemsmentioning
confidence: 99%
“…The selection criteria for the target stars were described in Marcy et al (2005). The stars were drawn from the Hipparcos catalog (ESA 1997) with criteria that they have B À V > 0:55, have decl: > À35 , be older than 2 Gyr, and reside within 3 mag of the main sequence.…”
Section: The Target Stars and Doppler Techniquementioning
confidence: 99%
“…The sixth column gives the mass of the star, as determined above from the Girardi et al (2002) models. The seventh column gives the logarithm of the fraction of the stellar luminosity that emerges as chromospheric emission at the Ca ii H and K lines, namely, log R 0 HK , and the eighth column gives the resulting photospheric jitter in m s À1 , estimated as described in Marcy et al (2005) and Wright et al (2005). The ninth and tenth columns give the expected rotation period and age of the star based on R 0 HK from Wright et al (2004) and Noyes et al (1984).…”
Section: The Target Stars and Doppler Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…These simulations were performed for all stars in the Anglo-Australian and Keck Planet Searches (for samples see Jones et al 2002;Marcy et al 2005;Butler et al 2006 and references therein), which show a long term radial-velocity profile consistent with an orbiting low-mass companion.…”
Section: Target Selectionmentioning
confidence: 99%